Lactic Fermentation as a Strategy to Improve the Nutritional and Functional Values of Pseudocereals - Rollán, Graciela C.; Gerez, Carla L.; LeBlanc, Jean G. (Frontiers in Nutrition, 2019)
Today, one of the greatest challenges worldwide is to reduce desnutrition and malnutrition while promoting sustainable agricultural and food systems. This is a daunting task due to the constant population growth and the profound changes in the demand for functional and higher nutritional value foods by consumers. Cereal grains are the most important dietary energy source globally; wheat, rice and maize currently provide about half of the dietary energy source of humankind. In addition, the increase of celiac patients worldwide has motivated the development of gluten-free foods using alternative flour types to wheat such as rice, corn, cassava, soybean and pseudocereals (amaranth, quinoa and buckwheat). Amaranth and quinoa have been cultivated since ancient times and were two of the major crops of the Pre-Colombian cultures in Latin- America. In recent years and due to their well-known high nutritional value, phytochemical content with potential health benefits, they received much attention as ideal candidates for gluten-free products. The current knowledge about the importance of exploiting these grains in healthy and nutritious foods, forces us to rethink and develop adequate strategies for their processing. Fermentation is one of the most antique andeconomical methods of producing and preserving foods and can be easily employed for cereal processing. The nutritional and functional quality of cereal/pseudocereals can be improved by fermentation using Lactic Acid Bacteria (LAB). This review provides an overview on pseudocereal fermentation by LAB emphasizing the capacity of these bacteria to decrease antinutritional factors such as phytic acid, increase the functional value of phytochemicals such as phenolic compounds, and produce nutritional ingredients such as B-Group vitamins. The numerous beneficial effects of lactic fermentation of pseudocereals could be exploited to design novel foods or grain ingredients destined to human health targetting specific populations.